The Configuration of Older Users as Drivers of Innovation in the Design of Digital Technologies - Endter, Cordula; Merkel, Sebastian; Künemund, Harald (NOvation — Critical Studies of Innovation, 2022)
This paper develops hypotheses on the discovery of older people as "users" in the publicly funded development of digital technologies and underlying innovation policy motives. We then describe the effects of this innovation policy on the development of products and older people as their users in the context of Ambient Assisted Living (AAL). To this end, we reconstruct the involvement of users in two AAL funding programs, one at the European level and one at the national level (Germany). Based on this, we discuss the resulting consequences by describing how older people are configured as users in technology development with a focus on the concept of user-centered design (UCD) and what this configuration means for the developed technologies as well as for the older users. We describe how the participation of older people in technology development projects is a complex task that is not without controversy in social science research on user participation. We conclude by arguing for alternative technology development strategies and funding practices.